EVALUASI PROSEDUR PENERIMAAN KAS PADA RUMAH SAKIT UMUM DAERAH AERAMO KABUPATEN NAGEKEO - Nenu, Anastasia; Thalib, Sabra B W; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2021)
The purpose of this study was to determine the procedure for cash receipts at the Aeramo Regional General Hospital, Nagekeo Regency. The data used in this study is a description of qualitative data, namely knowing the procedure for cash receipts at the Aeramo Regional General Hospital. The data collected in this study are interviews and documentation. The problem that occurs at the Aeramo General Hospital is the procedure for receiving cash at the Aeramo general hospital, overall it can be categorized as quite good, but there are several things that must be considered with the cash receipt procedure that has not gone well due to lack of accuracy in the recording process, incompatibility of duties and authority, lack of job training to employees, which is carried out by the employees, resulting in a discrepancy between the existing cash and its recording and the discrepancy between transactions. The results of the research that took place at the Aaeramo Regional General Hospital, Nagekeo Regency related to the cash receipts procedure had been going well, there were several things that needed attention, namely the cash receipt procedure still using the manual system. Therefore, the researcher suggests that parties can use information systems, in order to facilitate cash receipt transactions, so that rash houses do not create fraud.